DESAIN PROSES PEMBUATAN COATING FILM BERBASIS PATI SAGU (Metroxylon sp.) IKAT SILANGASAM SITRAT - Dyah Ayu Larasati, Indah Yuliasih, dan Titi Candra Sunarti (Jurnal Teknologi Industri Pertanian, 2017)
Starch is an important polysaccharide for coating film production. However, it has limitation since its hydrophilic, which reduce the physical mechanical characteristics of the coating film. The effort to overcome these weaknesses is by modifying the starch with cross liking method. In this study, sago was used as the source of starch with citric acid as its cross linking agent, and the filler material for film making using CMC and chitosan. The objective of this study was to design coating film production by using cross-linked sago starch to improve its properties. The stage of this study were the characterization of raw materials, formulation of coating film and its characterization. For CMC fillers, the result of coating film had a range of moisture value, tensile strength, elongation, water solubility, and water vapor transmission rate of 25-28%, 0.66-0.70 MPa, 11-15%, 54.9-74.9%, and 1.8-1.9 g/hour.mm2. For chitosan fillers, the coating film had a range of moisture values, tensile strength, elongation, water solubility, and water vapor transmission rates of 20-24%, 0.43-1.75 MPa, 13-17%, 23-41%, and 2.0-2.1 g/hour.mm2.Keywords: citric acid, coating film, crosslinking, formulation, process design, sago starch